2015
DOI: 10.1038/cmi.2015.35
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation is required for herpes simplex virus type I (HSV-1)-induced early phase interferon-beta production

Abstract: Type I interferons such as interferon-beta (IFN-β) play essential roles in the host innate immune response to herpes simplex virus type I (HSV-1) infection. The transcription of type I interferon genes is controlled by nuclear factor-κB (NF-κB) and interferon regulatory factor (IRF) family members including IRF3. NF-κB activation depends on the phosphorylation of inhibitor of κB (IκB), which triggers its ubiqitination and degradation. It has been reported that neddylation inhibition by a pharmacological agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…The results of the present study demonstrated that the neddylation inhibitor MLN4924 suppressed the proinflammatory cytokine production in neutrophils in a dose-dependent manner, which is consistent with that observed in mononuclear cells (6,19,20,28,37). In order to purify peritoneal neutrophils induced by 3% thioglycolate intraperitoneal injection, peritoneal cells were stained with PE-conjugated anti-mouse Gr1, followed by isolation with anti-PE antibody-coated magnetic microbeads (38).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The results of the present study demonstrated that the neddylation inhibitor MLN4924 suppressed the proinflammatory cytokine production in neutrophils in a dose-dependent manner, which is consistent with that observed in mononuclear cells (6,19,20,28,37). In order to purify peritoneal neutrophils induced by 3% thioglycolate intraperitoneal injection, peritoneal cells were stained with PE-conjugated anti-mouse Gr1, followed by isolation with anti-PE antibody-coated magnetic microbeads (38).…”
Section: Discussionsupporting
confidence: 63%
“…The degradation of IκB proteins is the key to NF-κB activity (42). Impaired degradation of IκBα upon neddylation inhibition has been attributed to the inhibitory effects of MLN4924 on cytokine production in macrophages and dendritic cells (6,19,20,37). Hence, MLN4924 blocks neddylation, thereby suppressing production of inflammatory cytokines by inhibiting the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Mice harboring loxP -flanked Uba3 or Nedd8 alleles ( Uba3 fl/fl or Nedd8 fl/fl ) on a C57BL/6 background have been described [ 53 ]. Foxo1 fl/fl mice on the C57BL/6 background and mice expressing Cre recombinase under the control of Lck promoter or tamoxifen-sensitive Cre ER T2 under the control of Cd4 promoter were purchased from The Jackson Laboratory (Bar Harbor, ME, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we speculated that neddylation should promote the HSV-1-induced production of type I interferons, and this hypothesis was confirmed in our study, which was recently published in Cellular & Molecular Immunology (Figure 1). 14 With primary macrophages deficient of the catalytic subunit of neddylation E1, we have provided the first evidence that neddylation indeed plays a role in type I interferon production. Interestingly, neddylation blockade only delays but does not completely abrogate HSV-1-induced p65 nuclear translocation.…”
mentioning
confidence: 88%
“…14 Consequently, the early phase type I interferon production in HSV-1 infection is much more impaired than the late phase. 14 Recently, the notion that the host also exploits the neddylation pathway to fight against virus infection has been supported by additional evidence. Zhang T et al reported that the polymerase basic protein 2 of influenza A virus can be covalently modified by NEDD8, which reduces its stability and blocks the replication of influenza A virus.…”
mentioning
confidence: 99%